Collectivist versus individualist mobility regimes? : structural change and job mobility in four countries - DiPrete, Thomas A. [Verfasser]; Graaf, Paul M. de [Verfasser]; Luijkx, Ruud [Verfasser]; Tahlin, Michael [Verfasser]; Blossfeld, Hans-Peter [Verfasser] (My University, 1997)
"Job mobility is produced by structural forces of expansion and contraction as well as by individual choices. But labor market structure and welfare state policies will create distinctive national patterns of labor force adjustment to shifts in technology, markets, and the consequent demand for particular forms of labor. In a four-nation comperative study, U.S. rates of job mobility showed the greatest sensitivity to structural change and to the labor market resources of individual workers. The Netherlands was at the opposite pole, with worker outcomes largely insulated from structural forces. Germany-s strong labor market boundaries channeled adjustment within sectors or between employment and nonemployment, while Sweden-s pattern was intermediate between that of the United States and Germany." (author-s abstract, IAB-Doku) In einem 4-Länder-Vergleich (USA, Niederlande, Schweden, Bundesrepublik Deutschland) wird die berufliche Mobilität bezüglich der Struktur und des Strukturwandels des Arbeitsmarktes und der wohlfahrtsstaatlichen Politik untersucht. (IAB)
Keywords: G 1.3.3.3 Mobilität; G 2.3.1 Arbeitsteilung & -organisation; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; I 2.3.2 Nordamerika; I 2.2.1 Westeuropa; Berufliche Mobilität; Arbeitsmarktstruktur; Auswirkung; Sozialpolitik; Arbeitskräftemobilität; Quantitative Angaben; Internationaler Vergleich; USA; Niederlande; Schweden; 1980-1994